2018
DOI: 10.1016/j.scitotenv.2018.06.271
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into the strategy for methane production affected by conductive carbon cloth in wetland soil: Beneficial to acetoclastic methanogenesis instead of CO2 reduction

Abstract: Conductive materials/minerals can promote direct interspecies electron transfer (DIET) between syntrophic bacteria and methanogens in defined co-culture systems and artificial anaerobic digesters; however, little is known about the stimulation strategy of carbon material on methane production in natural environments. Herein, the effect of carbon cloth, as a representative of conductive carbon materials, on methane production with incubated wetland soil was investigated. Carbon cloth significantly promoted meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 51 publications
3
31
0
2
Order By: Relevance
“…We sampled a soil from the Yellow River Delta [28,29]. Straw was thus used as the carbon source during pre-incubation for enriching methanogenic archaea.…”
Section: Soil Sample and Batch Experiments (Experiments 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…We sampled a soil from the Yellow River Delta [28,29]. Straw was thus used as the carbon source during pre-incubation for enriching methanogenic archaea.…”
Section: Soil Sample and Batch Experiments (Experiments 2)mentioning
confidence: 99%
“…where ΔG 0 is ΔG at 273.15 K and 101.325 kPa; R, the ideal gas constant, 8.3145 J•mol −1 •K −1 ; T, the absolute thermodynamic temperature, 303.15 K; C CH4 , C CO2 , and C H2 are concentrations of methane, CO 2 , and H 2 , respectively, mol•L −1 . The calculation of ΔG 0 was detailed referring to a previous study [28].…”
Section: Thermodynamic Analysismentioning
confidence: 99%
“…Örneğin Li ve ark. [38] yaptıkları bir çalışmada, karbon kaplamanın oksidasyon-redüksiyon reaksiyonlarına etkisini araştırmışlardır. Bu çalışmada karbon kaplama işlemiyle elektron transfer hızının arttığı gözlemlenmiştir.…”
Section: İletken Malzemeleri̇n Türler Arasindaki̇ Elektron Transferi̇ne unclassified
“…İletken malzeme kullanılarak AP ve metan üretim sürecinin geliştirilmesi ile ilgili çalışmalar genellikle sentetik substrat kullanılarak yapılmıştır [38]. Bu malzemelerin gerçek ortamlarda nasıl bir rol alacağı henüz tam olarak anlaşılamamıştır ve gelecekte bu yönde araştırmalar yapılması biyogaz tesislerinin veriminin iyileştirilmesi adına önemli adımlar olacaktır.…”
Section: İletken Malzemeleri̇n Türler Arasindaki̇ Elektron Transferi̇ne unclassified
“…Supplementing CM, specifically magnetite, could interestingly mediate the electron transfer among cells through substituting the pilus-associated cytochrome OmcS that are commonly found in G. sulfurreducens [25]. Li et al [26] observed an increase in electron transfer rate from 0.0017 ± 0.0003 to 0.0056 ± 0.0015 s −1 , as a result of carbon cloth supplementation. Additionally, DIET could be stimulated through the establishment of two electrodes inside AD reactor, under slight EV with/without the presence of CM [3,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%